Local Community Participation in The Management of Culinary Tourism at Jimbaran Beach - Ni Kadek Sintya Wulandari; Hartanti Woro Susianti; Anom Hery Suasapha (Journal of Tourism and Hospitality Analysis (JoTHA), 2026)
Jimbaran Beach is one of Bali’s leading culinary tourism destinations, offering not only a culinary experience but also economic opportunities for the local community. This study aims to identify the forms and types of local community participation in managing culinary tourism at Jimbaran Beach. The research employed a descriptive quantitative method with data collected through questionnaires. The population consisted of residents of Desa Adat Jimbaran, with a total sample of 96 people. The results show that the most dominant form of participation is labor, reflected in the community’s involvement in maintaining beach cleanliness.  The type of participation is categorized as Induced Participation, indicating that decision-making remains top-down and is not fully initiated by the community.